Motivational reserve: motivation-related occupational abilities and risk of mild cognitive impairment and Alzheimer disease - Forstmeier, Simon; Weyerer, Siegfried (Psychology and aging, 2012)
Midlife motivational abilities, that is, skills to initiate and persevere in the implementation of goals, have been related to mental and physical health, but their association with risk of mild cognitive impairment (MCI) and Alzheimer's disease (AD) has not yet been directly investigated. This relation was examined with data from the German Study on Ageing, Cognition, and Dementia in Primary Care Patients (AgeCoDe). A total of 3,327 nondemented participants (50.3% of a randomly selected sample) aged 75-89 years were recruited in primary care and followed up twice (after 1.5 and 3 years). Motivation-related occupational abilities were estimated on the basis of the main occupation (assessed at follow-up II) using the Occupational Information Network (O NET) database, which provides detailed information on worker characteristics and abilities. Cox proportional hazards models were used to evaluate the relative risk of developing MCI and AD in relation to motivation-related occupational abilities, adjusting for various covariates. Over the 3 years of follow-up, 15.2% participants developed MCI and 3.0% developed AD. In a fully adjusted model, motivation-related occupational abilities were found to be associated with a reduced risk of MCI (HR: 0.77; 95% CI: 0.64-0.92). Motivation-related occupational abilities were associated with reduced risk of AD in ApoE ε4 carriers (HR: 0.48; CI: 0.25-0.91), but not in noncarriers (HR: 0.99; CI: 0.65-1.53). These results suggest that midlife motivational abilities are associated with reduced risk of MCI in general and with reduced risk of AD in ApoE ε4 carriers. Revealing the mechanisms underlying this association may inform novel prevention strategies for decelerating cognitive decline in old age.